Mixture formation and combustion process analysis of an innovative diesel piston bowl design through the synergetic application of numerical and optical techniques. (1st February 2022) - Millo, F.; Piano, A.; Roggio, S.; Pastor, J.V.; Micó, C.; Lewiski, F.; Pesce, F.C.; Vassallo, A.; Bianco, A.
Highlights: Innovative diesel piston bowl design characterized through both numerical and experimental analysis. Numerical OH distribution reliably predicts the OH* chemiluminescence images. Innovative bowl showed remarkable improvements of the air/fuel mixing process. Potential soot reduction without any detrimental effect on engine efficiency was demonstrated. Abstract: The optimization of diesel engine piston bowl geometries has a crucial role in improving the near-wall flame evolution for better air/fuel mixing and soot reduction. With these aims, an innovative piston bowl for a light-duty diesel engine was designed, coupling both a sharp-stepped lip and radial bumps in the inner bowl rim. The impact of the proposed design was investigated through both 3D-CFD and single-cylinder optical engine. The numerical model, featuring a calibrated spray model and a detailed combustion mechanism, was used to analyse the non-reactive air/fuel mixing and the combustion processes. Results highlighted a reduced jet-to-jet interaction and better air/fuel mixing for the innovative bowl with respect to a conventional re-entrant design, thus enabling faster combustion process after the end of main injection. Numerical results in terms of flame's kinematic and oxidation process were compared with the combustion image velocimetry (CIV) and OH* chemiluminescence from the optical engine, showing higher velocity near the radial bumps, and faster flame recirculation towards the piston center. Moreover, both experiments and simulations showed a more intense OH distribution in the radial-bumps region and above the step during the first stage of the combustion process, thanks to the enhanced air/fuel mixing.